An active dose-measuring device for X-rays generated by ultra-short, ultra-intense laser pulses. (3rd March 2023) - Wang, Fengdie; Wang, Zhonghai; Wu, Yuchi; Wang, Shaoyi; Yan, Yonghong; Yu, Minghai; Zhang, Xiaohui; Wen, Jiaxing; Tan, Fang; Yang, Yue; Zhang, Jie; Zhou, Rong; et al.
Abstract: Ultra-short, ultra-intense laser pulses can create extreme physical conditions for a wide range of applications in atomic and molecular physics, materials chemistry, and inertial-confinement fusion. However, laser-matter interactions can be accompanied by significant X-ray emission that introduces radiation risks to the nearby environment and personnel. It is usually to monitor the radiation dose during in high-intensity laser-target interactions with optically stimulated luminescence and thermo-luminescence devices. However, these passive methods cannot measure the radiation dose in real time, while most active dosimeters cannot accurately measure pulsed radiation doses. Here, transient pulse X-ray radiation doses are converted by CdWO4 crystals into slow signals. Because the crystals have a 14-μs luminescence decay time, they can absorb sub-nanosecond X-ray pulses and release the energy at a 100-μs rate, thus reducing the linear-response pressure of subsequent devices. A pulse detector based on a CdWO4 crystal, a phototube, and a custom signal-processing circuit was developed. Experiments were performed at the 45-TW femtosecond laser facility of the Laser Fusion Research Center. The detector deviation was less than ±20% relative to that of an ionization-chamber detector. This initially verified its feasibility for real-time pulsed X-ray radiation detection.